Exploring the literary element ‘mood’ in an award-winning Malaysian picturebook: A multimodal analysis - Komathy Senathy Rajah; Cecilia Yin Mei Cheong (Studies in English Language and Education, 2022)
This article examines how an award-winning Malaysian picturebook for young learners entitled ‘The Magic Buffalo’ by Jainal Amambing utilizes visual and textual semiotic resources to develop the literary element ‘mood’. Knowledge of visual and textual meaning-making systems is necessary as it will enable young learners to achieve a deeper understanding of the literary element ‘mood’ in multimodal texts and also be visually literate. The literary element ‘mood’ is chosen because it helps to create the atmosphere and meaning of a story. In addition, this knowledge will also prepare young learners to deal with emotions in real life. The analysis is based on an adaptation of Painter et al.’s multimodal discourse analysis framework. The results of this study revealed that facial expression is the most prominent visual affect utilized in this picturebook, followed by bodily stance and ambiance respectively. The textual analysis reveals that the main character experiences an ongoing mental state, and un/happiness is the most commonly found emotion. The intermodal cohesion analysis clearly highlights how visual choices enhance the meaning provided by the textual choices. The use of visual symbols, facial expressions, and body posture help to corroborate and escalate the textual description of the characters’ emotional states. The study suggests that knowledge of visual and textual meaning systems will help young learners to critically analyse the literary element ‘mood’ and decode the meaning of multimodal texts.